Factors associated with depression, anxiety, stress and adverse neonatal outcomes among gestational diabetes mellitus patients in two hospitals in the Klang Valley, Malaysia - Lee, Kai Wei (2019)
Gestational diabetes mellitus (GDM) is defined as diabetes diagnosed for the first time during pregnancy. Prevalence of psychosocial problems among GDM women ranged from 0.6% to 62.8%. GDM and psychosocial illness could lead to adverse neonatal outcomes. The literature review showed that there were multiple associated factors for depression, anxiety or stress in pregnancy however the findings were inconsistent across studies. Study on depression, anxiety, stress and QOL among GDM patients is still scant in Malaysia and there was no study look into adverse neonatal outcomes among GDM mothers with depression, anxiety or stress. The general objective of this study was to determine the prevalence and factors associated with depression, anxiety, stress and adverse neonatal outcomes among GDM mothers in two hospitals in Klangvalley. Phase one was to conduct a systematic review and meta-analysis on the prevalence and associated factors for GDM in Asia. Four databases were used to search for the relevant studies using several search terms and inclusion criteria were applied. The second and third phase was a cross-sectional study on prevalence of depression, anxiety, stress and QOL and their adverse neonatal outcomes. Respondents’ socio-demographic characteristics and clinical profiles of respondents were obtained from maternal health records. DASS-21 and AsianDQoL questionnaires were used in this study. Pooled prevalence of GDM in Asia was 11.5%. and associated factors for GDM were past obstetrics history of GDM, congenital anomalies, macrosomia, stillbirth, abortion and preterm delivery, BMI ≥ 25 kg/m2, concurrent gestational hypertension, family history of diabetes, PCOS, age ≥ 25 years and multiparity ≥ 2. Prevalence of depression symptoms was 12.5% among GDM mothers. The associated factor for depression symptoms among GDM were being non-Muslim, have family history of depression and anxiety and EPHX2 (rs17466684) – AA genotype. The prevalence of anxiety symptoms in this study was 39.9%. Asthma history was an associated factor for anxiety symptoms among GDM mothers. The prevalence of stress symptoms is this study was 10.6%. The associated factor for stress symptoms among GDM mothers were allergy history, living without husband, have history of GDM, EPHX2 (rs17466684) – AA genotype, OXTR (rs53576) – AA/AG genotype and NRG1 (rs2919375) – TT/TC genotype. Percentage of poor to moderate QOL among GDM mothers was 23.2% and the associated factors were insulin with/out OHA and/or diet modification, have family history of depression and anxiety and have family history of GDM were associated factors for poor to moderate QOL among GDM mothers. Prevalence of adverse neonatal outcomes stood at 14.6% for low birth weight, preterm delivery (9.1%) macrosomia (4.8%), (9.3%) metabolic and electrolyte disorders, neonatal respiratory distress (5.3%) and congenital anomalies (2.4%). Presence of depression symptoms in GDM mothers, living without a husband, preterm delivery, having lower segment caesarean section, being nulliparous or primiparous and having family history of diabetes were associated factors for neonatal respiratory distress. This is the first study to look into the psychosocial aspect of GDM mothers in Malaysia and the first study that examine adverse neonatal outcomes born to GDM mothers with and without psychosocial illness.